Fabrication of niobium doped titanate nanoflakes with enhanced visible-light-driven photocatalytic activity for efficient ibuprofen degradation - Liu, Wen; Wei Zhang; Mushi Liu; Du, Penghui; Dang, Chenyuan; Jialiang Liang; Yunyi Li (Chinese Chemical Letters, 2019)
In this study, a novel class of niobium (Nb) doped titanate nanoflakes (TNFs) are fabricated through a one-step hydrothermal method. Nb doping affects the curving of titanate nanosheet, leading to the formation of nanoflake structure. In addition, Nb5+ filled in the interlayers of [TiO6] alters the light adsorption property of pristine titanate. The band gap of Nb-TNFs is narrowed to 2.85 eV, while neat titanate nanotubes (TNTs) is 3.4 eV. The enhanced visible light adsorption significantly enhances the visible-light-driven activity of Nb-TNFs for ibuprofen (IBP) degradation. The pseudo-first order kinetics constant for Nb-TNFs is calculated to be 1.04 h−1, while no obvious removal is observed for TNTs. Photo-generated holes (h+) and hydroxyl radicals (OH) are responsible for IBP degradation. The photocatalytic activity of Nb-TNFs depends on pH condition, and the optimal pH value is found to be 5. In addition, Nb-TNFs exhibited superior photo-stability during the reuse cycles. The results demonstrated Nb-TNFs are very promising in photocatalytic water purification.
Keywords: Element doping; Ibuprofen; Niobium; Photocatalysis; Titanate